2023
DOI: 10.3390/pathogens12020293
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Microbial Resistance Worldwide: Challenges over Controlling Life-Threatening Fungal Infections

Abstract: Fungal infections are a serious global concern because of their ability to spread and colonize host tissues in immunocompromised individuals. Such infections have been frequently reported worldwide and are currently gaining clinical research relevance owing to their resistant character, representing a bottleneck in treating affected people. Resistant fungi are an emergent public health threat. The upsurge of such pathogens has led to new research toward unraveling the destructive potential evoked by these spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 144 publications
0
13
1
1
Order By: Relevance
“…As cryptococcemia is a severe threat to the immunocompromised population, early detection and treatment are critical for better outcomes. 22 C. neoformans caused all cases; no C. gattii was detected in the present study. The studies showed that C. neoformans is predominantly reported worldwide and mainly infects immunosuppressed individuals, while the C. gattii is endemic to only a few regions of the world and infects immune-competent individuals.…”
Section: Discussioncontrasting
confidence: 68%
“…As cryptococcemia is a severe threat to the immunocompromised population, early detection and treatment are critical for better outcomes. 22 C. neoformans caused all cases; no C. gattii was detected in the present study. The studies showed that C. neoformans is predominantly reported worldwide and mainly infects immunosuppressed individuals, while the C. gattii is endemic to only a few regions of the world and infects immune-competent individuals.…”
Section: Discussioncontrasting
confidence: 68%
“…These compounds are present in the sphingolipid pathway, with phytosphingosine being an intermediate metabolite and sphingosine being an 18-carbon amino alcohol derived from the cleavage of ceramide process (27). The peak area corresponded to 2.8×10 6 for phytosphingosine (Figure 3F) and 5.4×10 4 for sphingosine (Figure 3G) in serum EVs from patients infected by C. albicans. Furthermore, in serum EVs from patients infected with C. neoformans, the peak area was 3.25×10 5 for sphingosine.…”
Section: Metabolite Annotations Of Serum Evs In Patient Samplesmentioning
confidence: 99%
“…Currently, most common fungal infections are invasive candidiasis (70%), cryptococcosis (20%), and aspergillosis (10%) (3). The emergence of fungal species resistant to the four classes of antifungal drugs (azoles, polyenes, echinocandins, and flucytosine) poses a serious challenge for the effective treatment of fungal infections (4, 5).…”
Section: Introductionmentioning
confidence: 99%
“…One of the most significant advances in medicine to date, the discovery of antibiotics in 1928 enabled the treatment of formerly deadly illnesses, saving millions of lives [1]. Microbial pathogen infections are a constantly rising concern with serious global ramifications, affecting millions of people every day and being a leading cause of mortality in both adults and children [2,3]. Antibiotics significantly reduced infection-related mortality, but misuse of them gave rise to the problem of antimicrobial resistance [4][5][6].…”
Section: Introductionmentioning
confidence: 99%